Sufficient provision for seekers of the path of truth [al ghunya li talibi tariq al haqq: a complete resource on the inner and outer aspects of Islam - Shaikh 'Abd Al Qaidr Al_Jilani (Al Baz Publishing, 1997)
isr, jil.1-5=c.1-5